KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN PERKEBUNAN KELAPA SAWIT DAN STATUS PERLINDUNGANNYA: STUDI KASUS KAWASAN UNIT PENGELOLAAN PT. ANUGERAH MAKMUR SEJATI, KABUPATEN KAPUAS HULU, KALIMANTAN BARAT - Harnios Arief (Media Konservasi, 2010)
AMS L.td region is part of Seberuang watershed ecosystem with heavily degraded condition, which was indicated by low levels of encounter with wildlife, both on observations during this study as well as from interviews with some of the people who live in the area. Protected areas such as river banks and peatland areas provided high opportunity of encounter with wildlife.  Field observation had resulted in the identification of 23 species of mammals, 54 species of birds, 11 species of reptiles. Further analyses showed that this region contains 13 species of mammals, 5 species of birds and 4 species of reptiles which fell in to rare/protected category. Keywords: ecosystems, habitats, wildlife, and wildlife species diversity.